TYPES AND SPREADING AREAS OF WEEDS SPREAD IN WINTER WHEAT FIELDS IN KARAKALPAKSTAN - Ajiniyazova Mekhriban Koylibaevna; Saymbetov Alisher, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This article presents the results of identifying the types of weeds spread in the fields where winter wheat is cultivated in the irrigated lands of the southern, central and northern regions of the Republic of Karakalpakstan. 16, 17, 15 families, 55, 46, 47 species, 63, 53, 52 types of weeds were detected in the southern region Amudarya, Khojeyli in the center, and Chimboy in the north, respectively.